Simulasi Reaktor MOCVD Dengan Menggunakan FEMLAB - Budi Mulyanti; Fitri S. Arsyad; Soegianto S; M. Barmawi; Sri Jatno W (Institut Teknologi Bandung, 2002)
Numerical simulation is presented in order to have optimal growth parameters when thin film GaN is grown in the MOCVD reactor. The simulation is performed by changing the growth parameters such as diffusivities and flow rates of gases, and the reactor’s geometries. Gases that are used in this simulation are trimethyl gallium (TMGa) and ammonia (NH3) as source gases and nitrogen (N2) as a carrier gas. The uniform thin film is obtained from this simulation, when the growth parameters are 0.1 m2s-1, 10-3ms-1, and 3.5 cm for gas diffusivity, gas flow rate and distance between reactor neck and substrate, respectively.